2018
DOI: 10.1063/1.5027591
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric performance enhancement of Pb(Mg1/3Nb2/3)O3-0.25PbTiO3 crystals by alternating current polarization for ultrasonic transducer

Abstract: The [001]-oriented Pb(Mg1/3Nb2/3)O3-0.25PbTiO3(PMN-0.25PT) single crystal has been poled by alternating current polarization (ACP). The piezoelectric, dielectric, and electromechanical properties of PMN-0.25PT crystals were investigated with the variations of the electric field, polarization frequency, and cycles. For the piezoelectric performance of the PMN-0.25PT crystal, the optimum ACP condition was obtained under the electric field of 12–18 kV/cm in the frequency range of 20–40 Hz and after 20 cycles. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(58 citation statements)
references
References 22 publications
0
58
0
Order By: Relevance
“…In addition, the AC-poled crystals exhibit a 30% enhancement in d 33 over the DC-poled crystals. This phenomenon was observed in many AC-poled relaxor-PT crystals 27,28,29,30 . To understand the mechanism for the enhanced piezoelectricity, we conducted phase-field simulations to calculate the piezoelectricity of PMN-28PT with different 71 o domain sizes, as shown in Fig.…”
mentioning
confidence: 65%
“…In addition, the AC-poled crystals exhibit a 30% enhancement in d 33 over the DC-poled crystals. This phenomenon was observed in many AC-poled relaxor-PT crystals 27,28,29,30 . To understand the mechanism for the enhanced piezoelectricity, we conducted phase-field simulations to calculate the piezoelectricity of PMN-28PT with different 71 o domain sizes, as shown in Fig.…”
mentioning
confidence: 65%
“…The enhancement of the piezoelectric and dielectric properties aer ACP are related to the optimization of the domain morphologies. 8,21,22,24 It should also be noted that 0.66PIN-0.34PT crystals have the rhombohedral perovskite phase. The ferroelectric crystals with the rhombohedral perovskite phase have eight spontaneous directions along h111i.…”
Section: Domain Structuresmentioning
confidence: 97%
“…Compared with PMN-PT crystals, the piezoelectric and dielectric properties of 0.66PIN-0.34PT crystals aer ACP are more dependent on frequency. The previous work revealed that the piezoelectric performances of PMN-PT and PIN-PMN-PT crystals can be signicantly improved using low frequency ACP, 29,30 22 The ACP process can reduce the energy required for domain rotation, which makes domain rotation easy. 28 The poling cycle is the process of the reduction of the energy required for domain rotation.…”
Section: Poling Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Large sized PMN-PT single crystals are grown mainly using the Bridgman technique [10][11][12]. Based on this technique, researchers have further managed to improve the di/piezoelectric properties of the PMN-PT system through some effective ways [13][14][15][16][17]. Hu et al [18] verified that the high-temperature poling technique was contributed to the enhanced piezoelectric properties.…”
Section: Introductionmentioning
confidence: 99%